MANAJEMEN PENGELOLAAN LINGKUNGAN BELAJAR PAUD BERBASIS MASYARAKAT - susanti, siti misra (Tumbuh Kembang, 2018)
Community based education management is the process of organizing, planning, leadership, and control of all resources, personnel, and materiel, in education based or community participation. Management cannotbe separated from planning, organizing, implementation (actuating) and controlling. In the management of learning environment, indoor or outdoor display early childhood education programs. The concept of the learning environment is very important for teachers.  Management of learning environments is an activity and means by which students can devote themselves to activities, create and explore and perform various activities that pose a number of activities. Cooperation institutions and the public is very important as learning not only focused in early childhood classroom environment but also children should give an understanding of the wider environment, for example the children invite to go to the farm, introducing tools of planting and explains plants that will planted. Early childhood institutions and community have collaboration to teach the children. Children not only know the concept but also the child directly to the practice field. Pestalozi proposed education must be followed and in line with the natural development of children. Every child should be given the opportunity to freely develop themselves, to know the natural environment, play with other children, and have a good relationship with parents, teachers, and the surrounding communities.